Preparative concentration of nucleic acids fragments by capillary isotachophoretic analyzer - Datinská, Vladimíra; Voráčová, Ivona; Berka, Jan; Foret, František (Journal of chromatography. A, 2018)
Sample preparation plays an important role in the DNA analysis workflow. Real samples often include a complex matrix, such as blood and other bodily fluids, or exogenous impurities, e.g., from the scene of crime. Most of the common nucleic acids isolation techniques are based on extractions; however, isotachophoretic focusing has recently attracted some interest for its simplicity and potential for very high enrichment factors and ease of automation. Here, we report on the use of a commercial isotachophoretic instrument for optimization of DNA focusing and preparative fraction collection. In order to achieve a high recovery and enrichment, experimental factors including electric current, sample amount and matrix were investigated experimentally as well as by computer simulation. The sample of a DNA ladder was injected in 30 μl volume and after ITP focusing the DNA zone was recovered using an on-column micropreparative collection valve. The DNA content in the collected sample was verified by fluorescence spectrometry and chip capillary electrophoresis with fluorescence detection.
Keywords: elektroforéza kapilární; izotachoforéza; Nucleic Acids; Electricity; DNA; Nucleic acids; Isotachophoresis; nukleové kyseliny; elektřina; Sample preparation; Electrophoresis, Capillary